Anode and zinc secondary battery
Patent Information
- Application Number
- JP2022566811
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-12
- Filing Date
- 2021-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-11-11
Smart Images

Figure 0007641990000003 
Figure 0007641990000004 
Figure 0007641990000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode and a zinc secondary battery. [Background technology]
[0002] In zinc secondary batteries such as nickel-zinc secondary batteries and air-zinc secondary batteries, it is known that metallic zinc precipitates in the form of dendrites from the negative electrode during charging, penetrates the voids in the separator such as nonwoven fabric, and reaches the positive electrode, resulting in a short circuit. Such a short circuit caused by zinc dendrites shortens the repeated charge-discharge life.
[0003] In order to address the above problems, a battery has been proposed that includes a layered double hydroxide (LDH) separator that selectively allows hydroxide ions to pass through while preventing the penetration of zinc dendrites. For example, Patent Document 1 (WO 2013 / 118561) discloses that an LDH separator is provided between the positive and negative electrodes in a nickel-zinc secondary battery. In addition, Patent Document 2 (WO 2016 / 076047) discloses a separator structure that includes an LDH separator fitted or joined to a resin outer frame, and that the LDH separator has such high density that it is gas impermeable and / or water impermeable. This document also discloses that the LDH separator can be composited with a porous substrate. Furthermore, Patent Document 3 (WO 2016 / 067884) discloses various methods for obtaining a composite material by forming an LDH dense membrane on the surface of a porous substrate. This method includes the steps of uniformly attaching an initiator substance capable of providing an initiation point for the crystal growth of LDH to a porous substrate, and subjecting the porous substrate to hydrothermal treatment in a raw material aqueous solution to form a dense LDH membrane on the surface of the porous substrate.
[0004] Meanwhile, another factor that shortens the life of zinc secondary batteries is the change in the morphology of zinc, which is the negative electrode active material. That is, as zinc dissolves and precipitates repeatedly due to repeated charging and discharging, the morphology of the negative electrode changes, causing high resistance due to blockage of pores, a decrease in the charge active material due to accumulation of isolated zinc, etc., resulting in a problem that charging and discharging becomes difficult. In order to address this problem, Patent Document 4 (WO 2020 / 049902) proposes using ZnO particles in combination with at least two selected from (i) metal Zn particles of a predetermined particle size, (ii) a predetermined metal element, and (iii) a binder resin having a hydroxyl group for use in the negative electrode. It is said that this negative electrode can suppress the deterioration of the negative electrode due to repeated charging and discharging in a zinc secondary battery, improve durability, and thereby extend the cycle life.
[0005] Furthermore, Patent Document 5 (Japanese Patent No. 6,190101) discloses a negative electrode composite material that contains a negative electrode active material such as metallic Zn or ZnO; a polymer such as an aromatic group-containing polymer, an ether group-containing polymer, or a hydroxyl group-containing polymer; and a conductive assistant that is a compound of elements such as B, Ba, Bi, Br, Ca, Cd, Ce, Cl, F, Ga, Hg, In, La, or Mn. It is described that the negative electrode composite material is suitable for forming a storage battery that exhibits excellent battery performance such as high cycle characteristics, rate characteristics, and Coulombic efficiency while suppressing shape changes in the electrode active material, morphological changes in the electrode active material such as dendrites, dissolution, corrosion, and passivation. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 118561 [Patent Document 2] International Publication No. 2016 / 076047 [Patent Document 3] International Publication No. 2016 / 067884 [Patent Document 4] International Publication No. 2020 / 049902 [Patent Document 5] Patent No. 6190101 Summary of the Invention
[0007] However, the charge-discharge cycle performance of existing zinc secondary batteries is not necessarily sufficient, and further improvement in the charge-discharge cycle performance is required.
[0008] The present inventors have now discovered that the cycle life can be extended by using a composite material for a negative electrode that contains a nonionic water-absorbing polymer together with Zn particles and ZnO particles, and in which at least a portion of the ZnO particles is covered with the nonionic water-absorbing polymer.
[0009] Therefore, an object of the present invention is to provide a negative electrode that can extend the cycle life of a zinc secondary battery.
[0010] According to one aspect of the present invention, there is provided a negative electrode for use in a zinc secondary battery, comprising: A negative electrode active material including ZnO particles and Zn particles; A nonionic water-absorbing polymer; wherein at least a portion of the ZnO particles are covered with the nonionic water-absorbing polymer.
[0011] According to another aspect of the present invention, A positive electrode and The negative electrode; a separator that separates the positive electrode and the negative electrode in a manner capable of conducting hydroxide ions; An electrolyte; A zinc secondary battery is provided, comprising: [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a ZnO particle partially covered with a nonionic water-absorbing polymer in the negative electrode of the present invention. [Figure 2A]FIG. 2 is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a charging reaction of a negative electrode according to the present invention, and is a diagram showing a state at an early stage of charging. [Figure 2B] FIG. 2B is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a charging reaction of a negative electrode according to the present invention, and is a diagram showing a state in the middle of charging following FIG. 2A. [Figure 2C] FIG. 2B is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a charging reaction of a negative electrode according to the present invention, and is a diagram showing a state in a later stage of charging following FIG. 2B. [Figure 3A] FIG. 2 is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a discharge reaction of a negative electrode according to the present invention, and is a diagram showing a state at the start of discharge. [Figure 3B] FIG. 3B is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a discharge reaction of a negative electrode according to the present invention, and is a diagram showing a state during discharge progress subsequent to FIG. 3A. [Figure 4] 1 is a graph showing an example of the relationship between the amount of water absorbed and the amount of KOH collected per 1 cm 3 of nonionic water-absorbing polymer, and the KOH concentration. [Diagram 5] 1 is an image of a cross section of a negative electrode in Example 5 observed by FE-SEM. [Figure 6] 6 is an EDX elemental mapping image of a cross section of the negative electrode shown in FIG. 5. [Figure 7] 1 is an image of a cross section of a negative electrode in Example 1 (comparison) observed by FE-SEM. [Figure 8] 1 is an image of a cross section of a negative electrode in Example 6 observed by FE-SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] negative electrode The negative electrode of the present invention is a negative electrode used in a zinc secondary battery. This negative electrode includes a negative electrode active material and a nonionic water-absorbing polymer. The negative electrode active material includes ZnO particles and Zn particles. FIG. 1 shows one embodiment of the ZnO particles and the nonionic water-absorbing polymer in the negative electrode of the present invention. As shown in FIG. 1, in the negative electrode according to the present invention, at least a part of the ZnO particles 12 is covered with the nonionic water-absorbing polymer 14. By using a composite material containing the nonionic water-absorbing polymer 14 together with the Zn particles and the ZnO particles 12 and at least a part of the ZnO particles 12 is covered with the nonionic water-absorbing polymer 14 in the negative electrode, the cycle life can be extended.
[0014] As mentioned above, in the conventional negative electrode, as zinc dissolves and precipitates repeatedly due to repeated charging and discharging, the morphology of the negative electrode changes, causing high resistance due to blockage of pores and a decrease in the charge active material due to accumulation of isolated zinc, which results in problems such as difficulty in charging and discharging. Such problems can be effectively suppressed or solved by adding a nonionic water-absorbing polymer to the negative electrode so as to cover at least a part of the ZnO particles. Although the mechanism is not necessarily clear, it is believed that the addition of the nonionic water-absorbing polymer makes the charge reaction and discharge reaction uniform, thereby suppressing the segregation or accumulation of zinc.
[0015] That is, during the charging reaction, ZnO + H2O + 2e - →Zn+2OH - As the charging reaction progresses, the OH - The concentration of OH on the negative electrode surface is close to that of the separator. -The concentration of zinc is higher than that of zinc ions. As a result, the above reaction on the surface of the negative electrode proceeds, while the reaction inside the negative electrode slows down. In this way, the charging reaction in the conventional negative electrode becomes non-uniform, which is thought to cause zinc segregation. On the other hand, in the negative electrode 10 of the present invention, as shown in FIG. 1, at least a part of the ZnO particles 12 is covered with the nonionic water-absorbing polymer 14. In this respect, since the nonionic water-absorbing polymer 14 does not have ion permeability, the reactive part 12a of the ZnO particles 12 is limited to a part that is not in contact with the nonionic water-absorbing polymer 14. It is thought that the charging reaction is made uniform by limiting the reactive part 12a of the ZnO particles 12 in this way. Specifically, it is speculated that the charging reaction in the negative electrode 10 of the present invention proceeds as follows. Here, the reactions of the negative electrode in the early charging stage, the middle charging stage, and the late charging stage are shown in FIGS. 2A to 2C, respectively. First, in the early charging stage shown in FIG. 2A, OH around the negative electrode 10 is ion-permeable. - Since the concentration is low, the reaction proceeds throughout the negative electrode 10, regardless of whether it is inside (close to the current collector 16) or on the surface (far from the current collector 16). In the middle stage of charging shown in FIG. 2B, the OH - As the concentration increases, the reaction inside the negative electrode 10 slows down, and OH - The reaction proceeds preferentially on the surface of the negative electrode 10 where the concentration is low. On the other hand, in the later stage of charging shown in FIG. 2C, the ZnO particles 12 are covered with the nonionic water-absorbing polymer 14, so that the reactive area on the surface of the negative electrode 10 is reduced. This causes the reaction to proceed again inside the negative electrode 10, and the charging reaction is made uniform. As a result, it is believed that the segregation of zinc is suppressed, and the cycle life can be extended.
[0016] During the discharge reaction, Zn+2OH - →ZnO+H2O+2e - As the discharge reaction progresses, the OH -The concentration of zinc in the negative electrode is lower than that on the surface of the negative electrode close to the separator, and the reaction inside the negative electrode slows down. For this reason, it is believed that the reaction becomes non-uniform in conventional negative electrodes, causing zinc to accumulate. In contrast, in the negative electrode 10 of the present invention, the nonionic water-absorbing polymer 14 conveniently absorbs water, thereby contributing to the continuation of the reaction inside the negative electrode 10. Here, conceptual diagrams showing the liquid absorption ability of the nonionic water-absorbing polymer 14 at the start and progress of the discharge reaction in the negative electrode 10 of the present invention are shown in Figures 3A and 3B, respectively. As shown in Figure 3A, at the start of the discharge reaction, OH in the electrolyte 18 is - Since the concentration is high, the above-mentioned discharge reaction proceeds regardless of whether it is on the surface or inside the negative electrode 10. As the discharge reaction proceeds, water is produced and the OH - The concentration decreases (i.e., the pH decreases). In this regard, as shown in FIG. 3B, as the pH decreases, the nonionic water-absorbing polymer 14 increases its liquid absorption ability, and absorbs the water generated by the negative electrode active material, thereby assisting the above-mentioned discharge reaction. In other words, the nonionic water-absorbing polymer 14 conveniently absorbs water from the discharge reaction in which water is generated, so that the discharge reaction continues inside the negative electrode 10 and the discharge reaction is uniformed. As a result, it is considered that the accumulation of zinc is suppressed and the cycle life can be extended. The advantageous effect of the present invention described above is a unique effect due to the selection of the nonionic water-absorbing polymer 14. In fact, when an ionic absorbent polymer (e.g., polyacrylic acid or potassium polyacrylate) is added, the above-mentioned effect is not obtained, and the cycle characteristics are rather reduced.
[0017] The negative electrode active material includes Zn particles (not shown) and ZnO particles 12. The Zn particles are typically metal Zn particles, but particles of a Zn alloy or a Zn compound may be used. The metal Zn particles may be metal Zn particles generally used in zinc secondary batteries, but it is more preferable to use metal Zn particles smaller than the metal Zn particles in terms of extending the cycle life of the battery. Specifically, the average particle size D50 of the metal Zn particles is preferably 5 to 200 μm, more preferably 50 to 200 μm, and even more preferably 70 to 160 μm. The preferred content of the Zn particles in the negative electrode 10 is preferably 1.0 to 87.5 parts by weight, more preferably 3.0 to 70.0 parts by weight, and even more preferably 5.0 to 55.0 parts by weight, when the content of the ZnO particles 12 is 100 parts by weight. The metal Zn particles may be doped with a dopant such as In or Bi. The ZnO particles 12 are not particularly limited and may be a commercially available zinc oxide powder used in zinc secondary batteries or a zinc oxide powder obtained by growing particles from the commercially available zinc oxide powder as a starting material through a solid-phase reaction or the like. The average particle size D50 of the ZnO particles 12 is preferably 0.1 to 20 μm, more preferably 0.1 to 10 μm, and even more preferably 0.1 to 5 μm. In this specification, the average particle size D50 refers to a particle size at which the cumulative volume from the small particle size side in a particle size distribution obtained by a laser diffraction / scattering method is 50%.
[0018] The negative electrode 10 preferably further contains one or more metal elements selected from In and Bi. These metal elements can suppress the generation of undesirable hydrogen gas due to self-discharge of the negative electrode 10. These metal elements may be contained in the negative electrode 10 in any form such as metal, oxide, hydroxide, other compound, etc., but are preferably contained in the form of oxide or hydroxide, and more preferably in the form of oxide particles. Examples of the oxides of the above metal elements include In2O3, Bi2O3, etc. Examples of the hydroxides of the above metal elements include In(OH)3, Bi(OH)3, etc. In any case, when the content of the ZnO particles 12 is 100 parts by weight, the content of In is preferably 0 to 2 parts by weight in terms of oxide, and the content of Bi is preferably 0 to 6 parts by weight in terms of oxide, and more preferably the content of In is 0 to 1.5 parts by weight in terms of oxide, and the content of Bi is preferably 0 to 4.5 parts by weight in terms of oxide. When In and / or Bi are contained in the negative electrode 10 in the form of oxide or hydroxide, it is not necessary that all of In and / or Bi are in the form of oxide or hydroxide, and a part of them may be contained in the negative electrode in other forms such as metal or other compounds. For example, the above metal elements may be doped into metal Zn particles as trace elements. In this case, the In concentration in the metal Zn particles is preferably 50 to 2000 ppm by weight, more preferably 200 to 1500 ppm by weight, and the Bi concentration in the metal Zn particles is preferably 50 to 2000 ppm by weight, more preferably 100 to 1300 ppm by weight.
[0019] The nonionic water-absorbing polymer 14 can be any commercially available nonionic water-absorbing polymer, but as described above, it is preferable that the polymer has a property that the liquid absorption property changes according to the change in pH. 34 shows an example of the relationship between the amount of water absorbed and the amount of KOH collected per unit time and the KOH concentration. As shown in FIG. 4, the amount of water absorbed changes with the change in the KOH concentration in the electrolyte (i.e., the change in pH), but a material that does not change the amount of KOH collected significantly is preferred in that it can absorb or release only water with pH fluctuation. In particular, a material that exhibits a behavior in which the amount of water absorbed decreases with an increase in pH is preferred. Preferred examples of such nonionic water-absorbing polymers 14 include polyalkylene oxide-based water-absorbing resins, polyvinyl acetamide-based water-absorbing resins, polyvinyl alcohol (PVA resin), and polyvinyl butyral (PVB resin), and more preferably polyalkylene oxide-based water-absorbing resins. As the polyalkylene oxide-based water-absorbing resin, commercially available products can be used. The nonionic water-absorbing polymer 14 may contain at least one selected from hydrophilic ether groups, hydroxyl groups, amide groups, and acetamide groups. The presence of these functional groups makes it possible to obtain a water-absorbing and releasing function that is more favorable for the battery reaction.
[0020] In the negative electrode 10, the nonionic water-absorbing polymer 14 covers at least a part of the ZnO particle 12. That is, the nonionic water-absorbing polymer 14 may cover a part of the surface of the ZnO particle 12 as shown in FIG. 1, or may cover the entire surface of the ZnO particle 12. The nonionic water-absorbing polymer 14 may cover not only the ZnO particle 12 but also at least a part of the Zn particle. The coverage of the ZnO particle 12 by the nonionic water-absorbing polymer 14 is preferably 2 to 99%, more preferably 4 to 75%, even more preferably 16 to 75%, particularly preferably 49 to 75%, and most preferably 55 to 68%. In the present invention, the coverage of the ZnO particle 12 means the ratio (%) of the length of the portion where the ZnO particle 12 and the nonionic water-absorbing polymer 14 contact each other to the length of the outer periphery of the ZnO particle 12 when the cross section of the negative electrode 10 is image-analyzed. The coverage of the ZnO particles 12 can be preferably calculated according to the procedure shown in Evaluation 2 of the Examples described later.
[0021] There is no particular limitation on the method for coating the ZnO particles 12 with the nonionic water-absorbing polymer 14. For example, the ZnO particles 12 can be preferably coated with the nonionic water-absorbing polymer 14 by using any one of the following methods (a) to (d). (a) A mixed powder containing Zn particles, ZnO particles 12, a nonionic water-absorbing polymer 14, and a binder (e.g., polytetrafluoroethylene) is prepared. This mixed powder is heated and kneaded together with a solvent (e.g., propylene glycol, isopropyl alcohol) at a predetermined temperature (e.g., a temperature equal to or higher than the melting point of the nonionic water-absorbing polymer 14). (b) The nonionic water-absorbing polymer 14 is dissolved in a solvent at a predetermined temperature. The solvent in which the nonionic water-absorbing polymer 14 is dissolved is added to the ZnO particles and the Zn particles, and after mixing in a pot mill or the like, the mixture is dried to obtain a polymer-coated powder. Then, the obtained polymer-coated powder and the binder resin are kneaded together with the solvent. (c) To a mixed powder containing Zn particles, ZnO particles 12, and a binder resin, a nonionic water-absorbing polymer 14 is added in a state of being dissolved in a solvent, and then these are kneaded. (d) The obtained negative electrode 10 is sealed and heated at a temperature equal to or higher than the melting point of the nonionic water-absorbing polymer 14 .
[0022] The melting point of the nonionic water-absorbing polymer is preferably 45° C. to 350° C., more preferably 45° C. to 200° C., and even more preferably 50° C. to 100° C. In addition, the content of the nonionic water-absorbing polymer 14 in the negative electrode 10 is preferably 0.01 to 6.0 parts by weight, more preferably 0.01 to 5.0 parts by weight, even more preferably 0.5 to 4.5 parts by weight, and particularly preferably 1.5 to 4.5 parts by weight, in terms of solid content, when the content of the ZnO particles 12 is taken as 100 parts by weight.
[0023] The negative electrode 10 may further include a conductive additive. Examples of the conductive additive include carbon, metal powder (such as tin, lead, copper, and cobalt), and precious metal paste.
[0024] The negative electrode 10 may further contain a binder resin (not shown). When the negative electrode 10 contains a binder, the shape of the negative electrode is easily maintained. As the binder resin, various known binders can be used, and preferred examples include polyvinyl alcohol (PVA) and polytetrafluoroethylene (PTFE). It is particularly preferred to use a combination of both PVA and PTFE as the binder.
[0025] The negative electrode 10 is preferably a sheet-shaped press-molded body. This can prevent the negative electrode active material from falling off and improve the electrode density, and can more effectively suppress the change in shape of the negative electrode 10. Such a sheet-shaped press-molded body can be produced by adding a binder to the negative electrode material and kneading it, and then subjecting the kneaded product to press molding such as roll pressing to form it into a sheet. The preferred kneading method for coating the ZnO particles 12 with the nonionic water-absorbing polymer 14 is as described above.
[0026] The negative electrode 10 is preferably provided with a current collector 16. Preferred examples of the current collector 16 include copper punched metal and copper expanded metal. In this case, for example, a mixture containing Zn particles, ZnO particles 12, nonionic water-absorbing polymer 14, and optionally a binder resin (e.g., polytetrafluoroethylene particles) can be applied onto the copper punched metal or copper expanded metal to preferably prepare a negative electrode plate consisting of the negative electrode 10 / current collector 16. In this case, it is also preferable to perform a press treatment on the negative electrode plate (i.e., the negative electrode 10 / current collector 16) after drying to prevent the negative electrode active material from falling off and improve the electrode density. Alternatively, the above-mentioned sheet-shaped press molded body may be pressure-bonded to the current collector 16 such as copper expanded metal.
[0027] Zinc secondary battery The negative electrode 10 of the present invention is preferably applied to a zinc secondary battery. Therefore, according to a preferred embodiment of the present invention, a zinc secondary battery is provided, which includes a positive electrode (not shown), a negative electrode 10, a separator that separates the positive electrode and the negative electrode 10 so as to be capable of conducting hydroxide ions, and an electrolyte 18. The zinc secondary battery of the present invention is not particularly limited as long as it is a secondary battery that uses the above-mentioned negative electrode 10 and the electrolyte 18 (typically an aqueous alkali metal hydroxide solution). Therefore, it can be a nickel-zinc secondary battery, a silver oxide zinc secondary battery, a manganese oxide zinc secondary battery, a zinc-air secondary battery, or any other type of alkaline zinc secondary battery. For example, it is preferable that the positive electrode contains nickel hydroxide and / or nickel oxyhydroxide, thereby forming a nickel-zinc secondary battery. Alternatively, the positive electrode may be an air electrode, thereby forming a zinc secondary battery.
[0028] The separator is preferably a layered double hydroxide (LDH) separator. That is, as described above, in the field of nickel-zinc secondary batteries and air-zinc secondary batteries, LDH separators are known (see Patent Documents 1 to 3), and this LDH separator can be preferably used in the zinc secondary battery of the present invention. The LDH separator can selectively allow hydroxide ions to pass through while preventing the penetration of zinc dendrites. In combination with the effect of the negative electrode of the present invention, the durability of the zinc secondary battery can be further improved. In this specification, the LDH separator is defined as a separator containing a layered double hydroxide (LDH) and / or an LDH-like compound (hereinafter collectively referred to as a hydroxide ion conductive layered compound), which selectively passes hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion conductive layered compound. In this specification, the "LDH-like compound" is a hydroxide and / or oxide having a layered crystal structure similar to LDH, which may not be called LDH, and can be said to be equivalent to LDH. However, in a broad sense, "LDH" can be interpreted as including not only LDH but also LDH-like compounds.
[0029] The LDH separator may be a composite with a porous substrate as disclosed in Patent Documents 1 to 3. The porous substrate may be made of any of ceramic materials, metal materials, and polymer materials, but is particularly preferably made of a polymer material. The polymer porous substrate has the following advantages: 1) flexibility (so it is difficult to break even if it is made thin); 2) it is easy to increase the porosity; 3) it is easy to increase the conductivity (because the thickness can be reduced while increasing the porosity); and 4) it is easy to manufacture and handle. Particularly preferred polymer materials are polyolefins such as polypropylene and polyethylene, which are excellent in hot water resistance, acid resistance, and alkali resistance, and are low cost, and most preferably polypropylene. When the porous substrate is made of a polymer material, it is particularly preferred that the hydroxide ion conductive layered compound is incorporated throughout the entire thickness of the porous substrate (for example, most or almost all of the pores inside the porous substrate are filled with the hydroxide ion conductive layered compound). In this case, the preferred thickness of the polymer porous substrate is 5 to 200 μm, more preferably 5 to 100 μm, and even more preferably 5 to 30 μm. As such a polymeric porous substrate, a microporous membrane such as that commercially available as a lithium battery separator can be preferably used.
[0030] The electrolyte 18 preferably contains an aqueous solution of an alkali metal hydroxide. Examples of the alkali metal hydroxide include potassium hydroxide, sodium hydroxide, lithium hydroxide, and ammonium hydroxide, with potassium hydroxide being more preferred. Zinc oxide, zinc hydroxide, and the like may be added to the electrolyte to suppress self-dissolution of the zinc-containing material.
[0031] LDH-like compounds According to a preferred embodiment of the present invention, the LDH separator may contain an LDH-like compound. The definition of the LDH-like compound is as described above. Preferred LDH-like compounds are: (a) a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al, or (b) a hydroxide and / or oxide having a layered crystal structure containing (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M which is at least one selected from the group consisting of In, Bi, Ca, Sr, and Ba; or (c) A hydroxide and / or oxide having a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, in which the LDH-like compound is present in the form of a mixture with In(OH)3.
[0032] According to a preferred embodiment (a) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, optionally Y, and optionally Al. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. For example, the LDH-like compound may further contain Zn and / or K. This can further improve the ionic conductivity of the LDH separator.
[0033] The LDH-like compound can be identified by X-ray diffraction. Specifically, when X-ray diffraction is performed on the surface of the LDH separator, a peak derived from the LDH-like compound is typically detected in the range of 5°≦2θ≦10°, more typically in the range of 7°≦2θ≦10°. As described above, LDH is a substance having an alternating laminate structure in which exchangeable anions and H2O exist as intermediate layers between stacked hydroxide basic layers. In this regard, when LDH is measured by X-ray diffraction, a peak due to the crystal structure of LDH (i.e., the (003) peak of LDH) is essentially detected at a position of 2θ=11 to 12°. In contrast, when an LDH-like compound is measured by X-ray diffraction, a peak is typically detected in the above-mentioned range shifted to the lower angle side from the above-mentioned peak position of LDH. In addition, the interlayer distance of the layered crystal structure can be determined by the Bragg formula using 2θ corresponding to the peak derived from the LDH-like compound in X-ray diffraction. The interlayer distance of the layered crystal structure constituting the LDH-like compound thus determined is typically 0.883 to 1.8 nm, and more typically 0.883 to 1.3 nm.
[0034] In the LDH separator according to the above aspect (a), the atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. The atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. The atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. The atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within the above ranges, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Regarding LDH separators, conventionally known LDHs have the general formula: M 2+ 1-x M3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0035] According to another preferred embodiment (b) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure, comprising (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Ti, Y, the additional element M, optionally Al, and optionally Mg. The additional element M is In, Bi, Ca, Sr, Ba, or a combination thereof. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferred that the LDH-like compound does not contain Ni.
[0036] In the LDH separator according to the above aspect (b), the atomic ratio of Ti / (Mg+Al+Ti+Y+M) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.50 to 0.85, more preferably 0.56 to 0.81. The atomic ratio of Y / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.20, more preferably 0.07 to 0.15. The atomic ratio of M / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.35, more preferably 0.03 to 0.32. The atomic ratio of Mg / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.10, more preferably 0 to 0.02. The atomic ratio of Al / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.04. Within the above range, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Incidentally, LDHs conventionally known as LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0037] According to yet another preferred embodiment (c) of the present invention, the LDH-like compound is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, and the LDH-like compound may be present in the form of a mixture with In(OH)3. The LDH-like compound of this embodiment is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, Y, optionally Al, and optionally In. The In that may be contained in the LDH-like compound may not only be that which is intentionally added to the LDH-like compound, but may also be that which is inevitably mixed into the LDH-like compound due to the formation of In(OH)3 or the like. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. Incidentally, LDHs conventionally known for LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. Therefore, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH.
[0038] The mixture according to the above embodiment (c) contains not only an LDH-like compound but also In(OH)3 (typically composed of an LDH-like compound and In(OH)3). The inclusion of In(OH)3 can effectively improve the alkali resistance and dendrite resistance of the LDH separator. The content of In(OH)3 in the mixture is preferably an amount that can improve the alkali resistance and dendrite resistance without substantially impairing the hydroxide ion conductivity of the LDH separator, and is not particularly limited. In(OH)3 may have a cubic crystal structure, or may have a structure in which In(OH)3 crystals are surrounded by the LDH-like compound. In(OH)3 can be identified by X-ray diffraction. EXAMPLES
[0039] The present invention will now be further illustrated by the following examples.
[0040] Examples 1-12 (1) Preparation of the positive electrode Paste-type nickel hydroxide positive electrode (capacity density: approx. 700 mAh / cm 3 ) was prepared.
[0041] (2) Preparation of the negative electrode The following various raw material powders were prepared. ZnO powder (Seido Chemical Industry Co., Ltd., JIS standard class 1 grade, average particle size D50: 0.2 μm) Metallic Zn powder (manufactured by DOWA Electronics Co., Ltd., doped with Bi and In, Bi: 70 ppm by weight, In: 200 ppm by weight, average particle size D50: 120 μm) Nonionic water-absorbing polymer (polyalkylene oxide-based water-absorbing resin, manufactured by Sumitomo Seika Chemicals Co., Ltd., Aquacaulk, grade: TWB-P, product form: powder, average particle size D50: 50 μm) - Ionic water-absorbing polymer (polyacrylic acid, manufactured by Sumitomo Seika Chemicals Co., Ltd., AQUPEC HV) · Ionic water-absorbing polymer (potassium polyacrylate, Sigma-Aldrich, Poly partial potassium salt)
[0042] 100 parts by weight of ZnO powder was added with 5.7 parts by weight of metal Zn powder, 1 part by weight of polytetrafluoroethylene (PTFE), and optionally a nonionic water-absorbing polymer or an ionic water-absorbing polymer in the blending ratios shown in Tables 1 and 2, and then heated and kneaded with propylene glycol. In this way, the nonionic water-absorbing polymer or the ionic water-absorbing polymer was dissolved in propylene glycol while kneading. The kneaded product was rolled with a roll press to obtain a negative electrode active material sheet. The negative electrode active material sheet was pressure-bonded to a tin-plated copper expand metal to obtain a negative electrode.
[0043] (3) Preparation of electrolyte Ion-exchanged water was added to a 48% aqueous potassium hydroxide solution (special grade, manufactured by Kanto Chemical Co., Ltd.) to adjust the KOH concentration to 5.4 mol%, and then 0.42 mol / L of zinc oxide was dissolved therein by heating and stirring to obtain an electrolyte.
[0044] (4) Preparation of evaluation cell The positive and negative electrodes were wrapped in nonwoven fabric, and a current extraction terminal was welded to them. The positive and negative electrodes thus prepared were placed opposite each other via an LDH separator, sandwiched between a laminate film with a current extraction port, and three sides of the laminate film were heat-sealed. An electrolyte was added to the cell container with the top open in this way, and the electrolyte was allowed to fully penetrate the positive and negative electrodes by evacuation or the like. The remaining side of the laminate film was then heat-sealed to form a simple sealed cell.
[0045] (5) Evaluation Rating 1 : State of nonionic water-absorbing polymer The cross-sections of the negative electrodes of Examples 1 to 8 were polished by a cross-section polisher (CP), and the cross-sections of the negative electrodes were observed by FE-SEM and EDX at a magnification of 30,000 times using a field emission scanning electron microscope (FE-SEM, Hitachi High-Tech, S-4800) equipped with an energy dispersive X-ray analyzer (EDX). FE-SEM images and EDX element mapping images obtained in Example 5 are shown in Figures 5 and 6, respectively. As shown in Figure 6, the EDX element mapping image confirmed that C and F were present in the negative electrode. In this regard, the negative electrodes of Examples 1 to 8 contain a nonionic water-absorbing polymer and PTFE as resins, and since PTFE contains F, it is believed that the part where only C was detected is derived from the nonionic water-absorbing polymer. As a result, it was confirmed that the nonionic water-absorbing polymer was present in a form that covered at least a part of the ZnO particles.
[0046] Rating 2 : Calculation of coverage For the negative electrodes of Examples 1 to 8, a field emission scanning electron microscope (FE-SEM, JSM-7900M, manufactured by JEOL Ltd.) was used to observe the cross section of the negative electrode at a magnification of 50,000 times (field of view: 2.3 μm × 1.6 μm). FE-SEM images of the cross sections of the negative electrodes obtained in Example 1 (comparison) and Example 6 are shown in Figures 7 and 8, respectively. The obtained FE-SEM images were imported into image processing software (Adobe Illustrator, manufactured by Adobe). Next, the length L1 of the portion where the ZnO particle and the nonionic water-absorbing polymer contact each other at the outer periphery of the ZnO particle included in the field of view, and the length L2 of the portion where the ZnO particle and the void (i.e., the portion where the nonionic water-absorbing polymer does not exist) contact each other were measured. Then, the following formula: [L1 / (L1+L2)]×100 The ratio (%) of the length of the contact part between the ZnO particle and the nonionic water-absorbing polymer to the length of the outer periphery of the ZnO particle was calculated, and the coverage of the ZnO particle was calculated. The results are shown in Table 1.
[0047] Rating 3 : Cycle characteristics Using a charge / discharge device (Toyo Systems Co., Ltd., TOSCAT3100), the simple sealed cell was subjected to formation at 0.1C charge and 0.2C discharge. Then, a 1C charge / discharge cycle was performed. The charge / discharge cycle was repeated under the same conditions, and the number of charge / discharge cycles until the discharge capacity of the prototype battery decreased to 70% of the discharge capacity of the first cycle was recorded and used as an index of cycle characteristics. The results are shown in Table 1, and it was confirmed that the cycle characteristics of the negative electrode to which a specified amount of nonionic water-absorbing polymer was added were improved by coating the ZnO particles with the nonionic water-absorbing polymer. In addition, it was confirmed from the results shown in Table 2 that the cycle characteristics were rather reduced when an ionic absorbent polymer was added.
[0048] [Table 1]
[0049] [Table 2]
Claims
1. A negative electrode for use in a zinc secondary battery, a negative electrode active material including ZnO particles and Zn particles; Nonionic water-absorbing polymers (excluding polyvinyl alcohol), Polytetrafluoroethylene as a binder resin; At least a portion of the ZnO particles is covered with the nonionic water-absorbing polymer; A negative electrode, wherein the coverage of the ZnO particles is 4 to 75%, and the coverage is a ratio of the length of a portion where the ZnO particles contact with the nonionic water-absorbing polymer to the length of the outer periphery of the ZnO particles when a cross section of the negative electrode is subjected to image analysis.
2. The negative electrode according to claim 1, wherein the coverage of the ZnO particles is 16 to 75%.
3. The negative electrode according to claim 1 or 2, wherein the coverage of the ZnO particles is 49 to 75%.
4. The negative electrode according to any one of claims 1 to 3, wherein the nonionic water-absorbing polymer is contained in an amount of 0.01 to 6.0 parts by weight in terms of solid content when the content of the ZnO particles is 100 parts by weight.
5. The nonionic water-absorbing polymer is at least one selected from the group consisting of polyalkylene oxide-based water-absorbing resin, polyvinyl acetamide-based water-absorbing resin, and polyvinyl butyral (PVB resin), the negative electrode according to any one of claims 1 to 4.
6. The negative electrode according to any one of claims 1 to 5, wherein the nonionic water-absorbing polymer is a polyalkylene oxide-based water-absorbing resin.
7. The negative electrode according to any one of claims 1 to 6, wherein the nonionic water-absorbing polymer has a property that the liquid absorption property changes according to a change in pH.
8. The negative electrode according to any one of claims 1 to 7, wherein the Zn particles are contained in an amount of 1.0 to 87.5 parts by weight per 100 parts by weight of the ZnO particles.
9. The negative electrode according to any one of claims 1 to 8, further comprising one or more metal elements selected from the group consisting of In and Bi.
10. The negative electrode according to any one of claims 1 to 9, wherein the negative electrode is a sheet-like press-molded body.
11. A positive electrode and The negative electrode according to any one of claims 1 to 10, a separator that separates the positive electrode and the negative electrode in a manner capable of conducting hydroxide ions; An electrolyte; A zinc secondary battery comprising:
12. 12. The zinc secondary battery according to claim 11, wherein the separator is an LDH separator comprising a layered double hydroxide (LDH) and / or an LDH-like compound.
13. The zinc secondary battery according to claim 12 , wherein the LDH separator is composited with a porous substrate.
14. The zinc secondary battery according to any one of claims 11 to 13, wherein the positive electrode contains nickel hydroxide and / or nickel oxyhydroxide, thereby making the zinc secondary battery a nickel-zinc secondary battery.
15. The zinc secondary battery according to any one of claims 11 to 13, wherein the positive electrode is an air electrode, thereby forming the zinc secondary battery into a zinc-air secondary battery.
Citation Information
Patent Citations
Method of manufacturing zinc electrode for alkaline storage battery
JP1978070348A
Nickellzinc storage battery
JP1979164230A
Polarization splitter
JP1986090101A
Zinc electrode for alkaline storage battery
JP1988245859A
Zinc electrode for alkaline storage battery and manufacture thereof
JP1990135664A